Hedging effectiveness of crude palm oil futures market in Malaysia / Nurul Asdaniah Azhar - Azhar, Nurul Asdaniah (2018)
This project paper is to study the relationship of hedging effectiveness of crude palm oil futures market in Malaysia from 2013 to 2017 monthly with 60 observations which traded under Bursa Malaysia Derivatives Berhad. Crude palm oil (CPO) is one of the important commodities of Malaysian economy. The impact of different variables on the futures crude palm oil price has seen the key issues for all the analysts. It has the significant role for enhancement the progress of the economy. Ordinary Least Squared (OLS) method was used to compute Minimum-Variance hedging ratio (MVHR), R-squared and hedging effectiveness by using monthly data from settlement price of crude palm oil futures contracts and spot price of crude palm oil. The data have taken from the Thomas Reuters Data Stream, Index Mundi and Malaysian Palm Oil Berhad based on 5 years period as the investigation. In overall, Malaysia FCPO market has a low level of hedging effectiveness (19% - 53%) due to less volatility of CPO spot price. As a conclusion, hedging effectiveness of crude palm oil futures market in Malaysia shows a low level of hedging effectiveness. This result indicates that the spot price of crude palm oil in Malaysia is relatively stable and consistent over the period of 2013 to 2017. The outcome of this research intends to provide hedging information of the Malaysia FCPO futures market in order to cover risk exposure by holding FCPO in BMD.